An Approach to Developing Internet of Things (IoT) － Based Services for Smart Museums - Ivanov, Rosen (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2019)
The aim of each museum is to present its exhibits in a way that enhances the visitor experience, satisfaction and knowledge. This objective is difficult to achieve, especially in museums with a very large number of exhibits and visitors. One possible solution is to use the modern Internet and mobile technologies in order to implement a service for personalized information delivery. The content that is delivered to visitors should be consistent with their preferences and free time. The paper presents an Internet of Things (IoT) － based solution for delivering personalized content to museum visitors, which includes: (1) Mobile app for visitors and curators; (2) Sensor network; and (3) Edge Computing Gateway. The main advantages of this solution are the following: platform independent service thanks to its full-stack JavaScript architecture; the service allows visitors to use it in multiple museums, not just in a particular museum; the service does not require permanent Internet access to operate; ability to deliver personalized content during the movement of visitors along the exhibits; relatively low price of the service thanks to the used hardware and open source software. Preliminary experiments in simulated and real environments show that proposed solution can be successfully used to create personalized content delivery services in smart museums.